Due To The Law On The Purchase of Land Rights That Have Not Been Certified If Bound By The Government Ah City of Surabaya (Case Study Number: 678 K/PID.SUS/2019 Jo 87/Pid.Sus/TPK/2018/PN.Sby - Abror Prima Putra; Moh.Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
The immovable property belongs to the state while related to administration, the control of the institution is used with the term â€œin beheerâ€ or â€œin controlâ€ where this can be evidence that the land parcel is under the control of a certain institution, and certain institutions are said to have a budget which appears from the government to finance the maintenance of the land parcels. Land is state or regional property, if this land is purchased or obtained at the expense of the APBN/APBD, or the land comes from other legitimate acquisitions, for example obtained through a grant/contribution, obtained as law or obtained based on court decisions that have legally binding. The purpose of being published is for the benefit of the right holder based on physical data and juridical data as registered in the land book. Meanwhile, uncertified land is land that does not have valid proof as a strong means of evidence regarding the physical data and juridical data contained.